Uncoded chronic kidney disease prevalence in secondary care: a retrospective audit with population health implications - Samantha Dolan; Ajitesh Anand; Philip A. Kalra; Stuart Stewart (BMC Nephrology)
Abstract Background One million patients are estimated to have undiagnosed chronic kidney disease (CKD) in England. Clinical coding in CKD is associated with improved management and lower acute kidney injury (AKI), unscheduled care and mortality risk. Primary care’s role in coding CKD is well documented. However, there is scant evidence on CKD coding quality in secondary care. Primary aims: to measure total and coded/uncoded CKD prevalence on admission and discharge, and conversion of uncoded to coded CKD in secondary care. Secondary aims: to map coding status to kidney health inequality themes and to measure predictors of coding, death and AKI. Methods Retrospective audit in an acute medical hospital ward in England, April 2022-February 2023. Descriptive statistics include counts/percentages for categorical data, prevalence estimates and rates. Logistic regression measured significant predictors (p = < 0.05) of receiving a diagnostic CKD code on discharge, risk of death, and of AKI. Results Uncoded CKD prevalence using discharge estimated GFR (eGFR) was 58.7% (n = 283), equating to 1.1 cases uncoded CKD per bed/month and 13.7 cases uncoded CKD per bed/year. Conversion of uncoded to coded CKD at discharge was only 6.7%. Hypertension and advanced CKD were significant predictors of coding CKD on discharge in uncoded patients. Age, sex, indices of multiple deprivation, and AKI were significant predictors of death during admission. Advanced CKD was a significant predictor of AKI during admission. Conclusions Uncoded CKD is highly prevalent in an acute medical hospital ward highlighting opportunity to improve coding in another part of the health system in addition primary care.